Static and evolutionary allometry in the Italian endemic ant species Cataglyphis italica (Emery 1906). Issue 1 (2nd January 2020) - Centorame, Massimiliano; Angelino, Davide; Bonanni, Roberto; Fanfani, Alberto
Abstract : Allometry is defined as differential growth of various body parts at distinct rates. Traditionally, two types of allometries have been studied in holometabolous insects: evolutionary and static. Polymorphic ants can represent a good model to study these two types of allometry. In this work, we investigated both static and evolutionary allometry in Cataglyphis species, focusing on the Italian endemic taxon Cataglyphis italica . We assessed: (i) the intracolonial size variability in C. italica ; (ii) the allometric relationships between body size, head size and leg size in C. italica ; (iii) evolutionary allometry in the Cataglyphis genus, by comparing the ratio of metafemur length to mesosoma length (a measure of body size) across nine species originated from two colonization routes: northern (from Asia to Europe) and southern (from Asia to North Africa). We found some evidence of allometric growth between body parts in workers of C. italica, particularly between body size and head size. Furthermore, in line with previous studies, we also found some evidence in support of evolutionary allometry in the Cataglyphis genus. Specifically, species originating in North Africa displayed significantly higher ratios of metafemur length (MFL) to mesosoma length (ML) than species originating in Europe, whereas the two groups of species did not differ with respect to MFL and ML. So, this result is consistent with the hypothesis that the evolution of longer legs relative to body size is an adaptation to more arid environmental conditions, allowing ants to optimize foraging efficiency.